Forecasting Rainfall in Planting Onion Crops in Brebes District, Brebes District Using Holt-Winters Exponential Smoothing - Nufus Mar'Atu Sholikhah Wasirudin; Dimara Kusuma Hakim (Politeknik Piksi Ganesha Indonesia, 2024)
Planting shallots is very dependent on rainfall. High rainfall when planting shallots can result in shallot plants not growing well, resulting in reduced selling value at harvest time and low rainfall. Therefore, this study aims to determine the rainfall forecasting process for planting shallot plants in Brebes District, Brebes Regency. The data used in rainfall forecasting is monthly data in Brebes District from January 2019 to December 2023 using the Holt-Winters Exponential Smoothing method. Data sourced from NASA's Power Data Access Viewer. In the surface data, get the MAPE value0.05241. Earth Skin Temperature data gets a MAPE value of 2.34346. Wind Speed data gets a MAPE value of 14.5396. DataPrecipitationgot a value of 138.829583. These findings contribute to further understanding regarding rainfall forecasting in shallot planting, which can support the planting process so that the harvest is good and produces high selling value.